Career Planning Profile of Vocational School Students in Bogor Regency: Comprehensive Perspective and Strategic Role of Career Guidance - Silvia Agustina; Mamat Supriatna; Eka Sakti Yudha (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study analyzes the career-planning profiles of Vocational High School students in Bogor Regency, an area with a growing industry but high unemployment among Vocational High School graduates. Using a quantitative descriptive survey, data were collected from 506 tenth-grade tourism students. A 46-item instrument was validated using the Rasch Model in Winstep software version 5.7.3, chosen for its detailed item fit analysis and for ensuring measurement reliability with ordinal data. Results showed that 72.13% of students were in the "Moderately Capable" category, suggesting basic awareness of career planning but limited practical execution. The psychomotor aspect scored lowest (31.65%), indicating a weak ability to translate career goals into action. No significant gender differences were found. These findings underscore the need for targeted interventions to strengthen students’ psychomotor skills. The study provides a foundation for designing career guidance programs tailored to the psychomotor aspect of vocational education in Bogor Regency. Keywords: career planning, vocational high school, guidance and counseling, career guidance, descriptive survey, bogor regency